Evolution of sex ratio through gene loss - Yin, Da (Proc Natl Acad Sci U S A, 2019)
The maintenance of males at intermediate frequencies is an important evolutionary problem. Several species of Caenorhabditis nematodes have evolved a mating system in which selfing hermaphrodites and males coexist. While selfing produces XX hermaphrodites, cross-fertilization produces 50% XO male progeny. Thus, male mating success dictates the sex ratio. Here, we focus on the contribution of the male secreted short (mss) gene family to male mating success, sex ratio, and population growth. The mss family is essential for sperm competitiveness in gonochoristic species, but has been lost in parallel in androdioecious species. Using a transgene to restore mss function to the androdioecious Caenorhabditis briggsae, we examined how mating system and population subdivision influence the fitness of the mss+ genotype. Consistent with theoretical expectations, when mss+ and mss-null (i.e., wild type) genotypes compete, mss+ is positively selected in both mixed-mating and strictly outcrossing situations, though more strongly in the latter. Thus, while sexual mode alone affects the fitness of mss+, it is insufficient to explain its parallel loss. However, in genetically homogenous androdioecious populations, mss+ both increases male frequency and depresses population growth. We propose that the lack of inbreeding depression and the strong subdivision that characterize natural Caenorhabditis populations impose selection on sex ratio that makes loss of mss adaptive after self-fertility evolves.